PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 005 SUNGAI SEGAJAH MAKMUR KECAMATAN KUBU KABUPATEN ROKAN HILIR - Ahmad Samsuddin; Lazim. N Lazim. N; Zulkifli Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This rsearch aims to improve the learning achievement of school year 2014/2015. The subjects of the research was the student class VB V SDN Sungai Segajah Makmur in number student 24 student. This research is Observational Action braze with two cycles. This observational data points out that learning process experiences step-up. It can be proven before action 60,92 worked up 16,69% as 71.09 on I. cycle on cycle II. worked up 38,50% as 84,38. Activity learns on first cycle appointment i. activity percentage learns as big as 59,37% by reducing category and worked up with percentage 78% by good categories on first meet cycle II. activity learns with percentage 87,50% by categories (very good) and increasing becomes 96,88% (very good). And analisis's result student activity data experience step-up on first meet i. cycle with percentage 55% by reducing category increases to become 78,12% by good categories, on first cycle appointment II. worked up as 82,14% and on appointment fourth increases to become 92,85% by pretty good categories. Observational result at brazes v SD Country 005 Sungai Segajah makmur of Affluent proves that learnings model implement Role Playing can increase ahasil student Social Science studying brazes VB SDN 005 Sungai Segajah Makmur.Keyword: Role Playing Learning model, learning achievement